Impact of heavy precipitation events on pathogen occurrence in estuarine areas of the Puzi River in Taiwan - Shih, Yi-Jia; Chen, Jung-Sheng; Chen, Yi-Jen; Yang, Pei-Yu; Kuo, Yi-Jie; Chen, Tsung-Hsien; Hsu, Bing-Mu (PloS one, 2021)
Pathogen populations in estuarine areas are dynamic, as they are subject to multiple natural and anthropogenic challenges. Heavy rainfall events bring instability to the aquatic environment in estuaries, causing changes in pathogen populations and increased environmental sanitation and public health concerns. In this study, we investigated the effects of heavy precipitation on the occurrence of pathogens in the Puzi River estuary, which is adjacent to the largest inshore oyster farming area in Taiwan. Our results indicated that Vibrio parahaemolyticus and adenovirus were the most frequently detected pathogens in the area. There was a significant difference (Mann-Whitney U test, p < 0.01) in water quality parameters, including total coliform, Escherichia coli , water temperature, turbidity, salinity, and dissolved oxygen, between groups with and without V . parahaemolyticus . In addition, the detection rate was negatively correlated with the average daily rainfall (r 2 > 0.8). There was no significant difference between water quality parameters and the presence/absence of adenovirus, but a positive correlation was observed between the average daily rainfall and the detection rate of adenovirus (r 2 ≥ 0.75). We conclude that heavy precipitation changes estuarine water quality, causing variations in microbial composition, including pathogens. As extreme weather events become more frequent due to climate change, the potential impacts of severe weather events on estuarine environments require further investigation.